The Effects of Removal Mineral Premix at Different Periods of Rearing on Performance, Carcass Yield and Tibia Bone of Broiler Chicks - Ebrahimnezhad, Y.; Hajihosseini, R.; Nazeradl, K.; Maheri-Sis, N.; Ghalehkandi, J. Ghiasi (Pakistan Journal of Nutrition, 2011)
This experiment was conducted to evaluate the effects of mineral premix removal from diet during different period (starter, 1-21 d; grower, 22-42 d and finisher, 43-49 d) on the performance of broilers. From the days of old, chicks a diet containing two levels of supplementary minerals premix (0 and 0.25%) received. The results showed that, between experimental groups in terms of feed intake during various periods were not differences. In the starter and grower periods weight gain among all treatments were not significantly, but during finisher period of experimental weight gain of remove mineral premix of starter and grower periods and remove mineral premix of all rearing periods treatments were significantly lower than other treatments (p